Knowledge towards health impacts of climate change among Amhara Sayint community, Northeastern Ethiopia - Genanew Mulugeta Kassaw; Asmamaw Malede; Adinew Gizeyatu; Metadel Adane; Asha Embrandiri; Awoke Keleb; Gete Berihun; Abebe Kassa Geto; Belachew Tekleyohannes Wogayehu; Gebremeskel Kibret Abebe; Tibebu Habtie Zewde; Sisay Abebe Debela; et al. (International Journal of Climate Change Strategies and Management, 2024)
Purpose – This study aims to assess the knowledge of Amhara Sayint district community in Northeastern Ethiopia towards the health impacts of climate change. Design/methodology/approach – A community-based cross-sectional study was conducted from 20 July to 5 September 2022, involving 605 randomly selected households in Amhara Sayint district, Northeastern Ethiopia. Data were collected through face-to-face interviews using a pilot-tested and content-validated questionnaire administered via Kobo Collect survey tool. The data were then exported to STATA for management and analysis. A proportional odds approach of ordinal logistic regression model was fitted with a 95% confidence level to identify factors associated with the community’s knowledge towards the health impacts of climate change. Findings – Of the total respondents, 3.47% (95% confidence interval [CI]: 2.1, 5.3) and 42.98% (95% CI: 38.9, 47) had inadequate and medium levels of knowledge towards the health impacts of climate change, respectively. Proportional odds model analysis result indicated that gender (female) (adjusted odds ratio [AOR] = 1.49; 95% CI: 1.053, 2.13), wealth status (poorest) (AOR = 1.97; 95% CI: 1.01, 3.83), educational status (unable to read and write) (AOR = 4.13; 95% CI: 1.25, 13.68) and participation status in environmental protection activities (not) (AOR = 1.78; 95% CI: 1.17, 2.71) were factors that significantly associated with inadequate and medium levels of knowledge towards the health impacts of climate change. Research limitations/implications – The result of this research is not supported by qualitative methods. Practical implications – Residents of the study area know the climate is changing; however, they lack adequate knowledge towards the health impacts of climate change. Social implications – Significant number of people have inadequate level of knowledge about health impacts of climate change so relevant health education is needed. Originality/value – This research is original in its focus on assessing public knowledge about the health impacts of climate change in the Amhara Sayint district, northeastern Ethiopia, a perspective often overlooked in existing studies. Its findings are crucial for guiding future research and developing targeted public health strategies and educational initiatives.